Analysis of Soil Vulnerability Level Due to Earthquake in Tarutung Region and Its Surroundings Using Probabilistic Seismic Hazard Analysis Method - Pratiwi, Nindya Mirandani; Lubis, Lailatul Husna; Sirait, Ratni Sirait; Sipayung, Reinhard Sipayung (Lambung Mangkurat University Press, 2024)
The geotectonic and geological conditions of the Tarutung region, which is crossed by the active Renun and Toru fault lines, cause the region to experience frequent earthquakes. Determination of the maximum ground acceleration (PGA) value is a very important method to see the vulnerability of the soil due to earthquakes in the region. This research uses the PSHA method with a probability of exceeding 2% PE for 50 years or a return period of 2500 years. The data used is earthquake data with a magnitude of 4.3 - 6.4 Mw and a depth of 10 - 250 km starting from 1971 - 2022. This data was obtained from two sources, namely the IRIS catalog and data from BMKG Geophysical Station Class I Deli Serdang. The vulnerability analysis obtained changes the value of peak ground acceleration in bedrock at the condition of T = 0 s (PGA), T = 0.2 s (short period), and T = 1 (long period) with a probability of exceeding 2% in 50 years in bedrock. The results of this study obtained maximum ground acceleration values of 0.3 g - 0.9 g for PGA (T = 0 s), 0.4 g - 0.9 g for a short period (T = 0.2 s), 1.0 g - 1.2 g for long period (T = 1 s). Areas with the highest ground acceleration values are located in Pahe Julu District, Pahae Jae District, and Simangumban District